ANALISIS KETERAMPILAN KREATIVITAS SISWA PADA MATERI GAYA DI KELAS IV SDN TUNJUNG 1 BANGKALAN - septiani, Ikanurma; Wijaya, Bagus Rahmad; Fijriyah, Izza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the creativity skills of fourth-grade students at SDN Tunjung 1 Bangkalan in understanding the concept of style in IPAS lessons. This study uses a descriptive quantitative approach with a saturated sampling technique involving all fourth-grade students as research subjects. Data were collected using a creative thinking skills test instrument that referred to four indicators, namely fluency, flexibility, originality, and elaboration. The results showed that the students' overall creative thinking skills were in the moderate category, with the following percentages for each indicator: fluency 49.3%, flexibility 59%, originality 55.5%, and elaboration 38%. The data showed that students were quite capable of generating various ideas and seeing problems from various perspectives, but still had difficulty expanding and developing ideas in depth. Therefore, it is recommended that future research focus on the development of learning devices that can stimulate the elaboration aspect, such as teaching modules, student worksheets (LKPD), or project based media tahat require students to explain and expand their ideas in detail.